Tren, Dampak, dan Tantangan Implementasi Artificial Intelligence dalam Pendidikan Dasar di Indonesia: A Systematic Literature Review - Mohamad Azhar Annawa UBM; Wulan Feronika Maharani; Lathif Abdul Razaq (Bima Journal of Elementary Education, 2026)
Low literacy and numeracy achievement, along with disparities in the quality of learning in Indonesia, necessitate adaptive technological innovations, one of which is the use of artificial intelligence (AI) in primary education. This study aims to map the forms and trends of AI implementation, analyze its impact on learning, and identify challenges and supporting factors at the primary education level (SD/MI). This study employed a Systematic Literature Review (SLR) approach following the PRISMA 2020 protocol, examining 153 accredited primary education journals (SINTA 1–6) published between 2022 and 2026, of which 16 articles met the inclusion criteria, with data analyzed through thematic coding and descriptive analysis. The results indicate that AI implementation remains at an early stage and is predominantly focused on the development of AI-based teaching media and instructional materials, while the use of adaptive platforms and pedagogical integration remains limited, with emerging trends including personalized learning, the strengthening of literacy and STEM, as well as the incorporation of local contexts. AI implementation has a positive impact on learning outcomes, cognitive skills, motivation, student engagement, as well as learning efficiency and teacher planning, although these effects may be influenced by the novelty effect. Key challenges include infrastructure limitations, teachers’ digital competencies, access disparities, and ethical concerns, while major supporting factors include school leadership and the flexibility of the Merdeka Curriculum. The limitations of this study lie in the limited number of studies and the predominance of descriptive research designs; therefore, future research is recommended to employ more rigorous designs and a broader scope.